New Directions in Pedagogy: Design, Playfulness, and STEAM (Editorial) - Drew, David E.; Tenhunen, Marja-Liisa; Wang, Maggie Minhong; Lee, Chien Sing *; Lau, Simon Boung Yew (Asia-Pacific Society for Computers in Education, 2018)
Massive technological, social and pedagogical changes are reshaping the nature of learning in the 21st Century. In this session at ICCE, researchers and scholars suggest new directions for education that take into account these innovations and that draw upon the latest theoretical developments about learning.